QUALITY OF LIFE OF PATIENTS WITH STRESS URINARY INCONTINENCE TREATED WITH TWO SURGICAL METHODS: A RANDOMIZED CONTROLLED STUDY (Zdravstveni glasnik, 2024)
Introduction: Static or stress urinary incontinence unquestionably in women has a significant negative impact on quality of life. Surgical treatment is the standard way of treating women with static stress incontinence, if the desired effect is not achieved with a conservative method of treatment.Objectives: To compare the quality of life of a group of patients with stress urinary incontinence surgically treated with Hammock method with the group treated by Needle method, and to compare the results with the quality of life of a healthy population of women.Methods: The study used the recommended questionnaire from the International Consultation on Incontinence, a short questionnaire ICIQ- SF. This questionnaire was used to collect data on symptomatology, frequency, amount of urine, and the impact on the quality of life before and after surgical treatment.Results: A statistically significant difference (p